Literature Review: Implementation Of Risk-Based Internal Audit On The Effectiveness Of Risk Management And Fraud Prevention - Darunifah, Okdiani; Prasetya Nugrahanti, Trinandari (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
An increasingly complex and dynamic organizational environment increases exposure to operational, financial, compliance, and strategic risks, potentially hindering the achievement of organizational goals. Weak risk management can create control gaps that encourage fraud. In this framework, risk-oriented internal auditing has surfaced as a tactical methodology that accentuates supervision of elevated-risk domains and bolsters the enhancement of governance, risk administration, and fraud deterrence. This research aims to examine the application of risk-based internal auditing (RBIA) to the effectiveness of risk management and fraud prevention, and to identify RBIA's role in supporting managerial decision-making and organizational sustainability. The investigation was executed via a scholarly review employing the Systematic Literature Review (SLR) methodology. The scholarly articles scrutinized were chosen from publications within the 2020–2025 timeframe that addressed risk-oriented internal auditing, risk governance, and fraud deterrence. The findings indicate that the implementation of Risk-Based Internal Auditing (RBIA) assumes a substantial role in enhancing the efficacy of risk governance by concentrating audits on high-risk domains and facilitating more judicious resource distribution. RBIA has additionally been demonstrated to assist in fraud deterrence by permitting early detection of potential fraudulent activities, assessing the efficacy of internal controls, and fortifying a culture of risk cognizance and organizational integrity.